The Role of Structural Funding for Stability in the German Banking Sector - Fabian Schupp; Leonid Silbermann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We analyze whether, and if so by how much, stable funding would have contributed to the financial soundness of German banks in the time period between 1995 and 2013, before the Basel III liquidity regulation to address excessive maturity mismatches in the wake of the financial crisis via the Net Stable Funding Ratio can be expected to have been fully implemented.
Keywords: G21; G28; C23; C25; 330